The Effect of Upcycled Brewers' Spent Grain on Consumer Acceptance and Predictors of Overall Liking in Muffins. (16th March 2022) - Combest, Shannon; Warren, Cynthia
Abstract : The brewing industry generates large amounts of food waste including brewers' spent grain (BSG) and leftover malted grains from beer production. BSG compositions can vary but consistently include high levels of protein and fiber. The potential nutritional and health benefits of BSG have sparked recent interest for food fortification. However, the challenges associated with BSG addition can impact food quality due to increases in fiber and protein content and reduction in starch content. Consumer testing was conducted to evaluate muffins containing varying levels of BSG (0, 20, 30% wt:wt flour) to determine the highest acceptable concentration on overall likeability, appearance, texture, moistness, sponginess, and taste attributes. Significant differences were found within appearance ( F = 7.728, P = .001) and taste ( F = 4.947, P = .008) ratings across all muffins. Control and 20% BSG muffins were rated significantly higher for appearance (6.74 ± 0.18; 6.64 ± 0.18) than 30% BSG muffins (6.11 ± 0.18). Muffins containing 20% BSG (7.15 ± 0.17) received significantly higher taste ratings than 30% BSG muffins (6.56 ± 0.22) and control muffins (6.49 ± 0.19). However, 30% BSG muffins maintained acceptance for all attributes showing higher allowable BSG substitutions than previously reported. Bivariate correlation analyses found that all attributes across each muffin variation were strongly, positively correlated ( r > 0.6) with overall likeability excluding appearance ( r = 0.359, P < 0.001) and moistness ( r = .466, P < 0.001) in control muffins. Significant predictors of overall likeability were appearance ( β = 0.088, P = 0.005), texture ( β = 0.181, P < 0.001), sponginess ( β = 0.226, P < 0.001), and taste ( β = 0.494, P < 0.001). Brewers' spent grain consumer acceptance results will guide the development of test food products for future human diet intervention compliance.